Therapeutic potential of mitochondrial uncouplers for the treatment of metabolic associated fatty liver disease and NASH - Leigh Goedeke; Gerald I. Shulman (Elsevier, 2021)
Background: Mitochondrial uncouplers shuttle protons across the inner mitochondrial membrane via a pathway that is independent of adenosine triphosphate (ATP) synthase, thereby uncoupling nutrient oxidation from ATP production and dissipating the proton gradient as heat. While initial toxicity concerns hindered their therapeutic development in the early 1930s, there has been increased interest in exploring the therapeutic potential of mitochondrial uncouplers for the treatment of metabolic diseases. Scope of review: In this review, we cover recent advances in the mechanisms by which mitochondrial uncouplers regulate biological processes and disease, with a particular focus on metabolic associated fatty liver disease (MAFLD), nonalcoholic hepatosteatosis (NASH), insulin resistance, and type 2 diabetes (T2D). We also discuss the challenges that remain to be addressed before synthetic and natural mitochondrial uncouplers can successfully enter the clinic. Major conclusions: Rodent and non-human primate studies suggest that a myriad of small molecule mitochondrial uncouplers can safely reverse MAFLD/NASH with a wide therapeutic index. Despite this, further characterization of the tissue- and cell-specific effects of mitochondrial uncouplers is needed. We propose targeting the dosing of mitochondrial uncouplers to specific tissues such as the liver and/or developing molecules with self-limiting properties to induce a subtle and sustained increase in mitochondrial inefficiency, thereby avoiding systemic toxicity concerns.